Distribution of macro-inclusions in low carbon aluminium-killed steel slabs. (9th August 2018) - Deng, Xiaoxuan; Ji, Chenxi; Dong, Wenliang; Li, Linping; Yin, Xue; Yang, Yindong; McLean, Alex
ABSTRACT: Macro-inclusions in low carbon, aluminium-killed steel slabs were characterised by step-machining within a 10 mm zone from the slab surface using an ASPEX automatic inclusion analyzer. Dendritic structures within the cross-section of slabs were examined. The results show that alumina clusters and alumina associated with bubbles are the dominant macro-inclusions. Along the slab width direction, macro-inclusions were mostly found at the slab centre because of the deeper hooks and freezing meniscus surrounding the submerged entry nozzle. In terms of slab thickness, inclusions were mainly concentrated within the zone 3.5–6 mm from the top of the slab surface, where the columnar dendrites showed a relatively small inclination angle, indicating small cross-flow velocities at the solidification front. The number density of macro-inclusions were strongly dependent on the washing effect produced by the flow velocity. High speed casting promotes this behaviour and improves the surface quality of the slabs.